Temporary transnational labour mobility and gendered individualization in Europe - Harsløf, Ivan; Zuev, Dennis (Mobilities, 2022)
In a context of a new transnational division of labour, temporary international labour mobility is on the rise in Europe. In particular, recent decades have seen considerably more women seeking work experience abroad. Observers have been concerned with how such mobility is related to individualization, and in particular how it may challenge collective institutions, communities and families. The aim of this study is to explore such issues among women and men with international work experience. Using data from European Social Survey, the paper investigates previously mobile workers in terms of their current working and living conditions. Across genders, we consider different forms of individualization that may be associated with transnational labour mobility. While both women and men with transnational work experience generally feature strong strategic individualization, this is most pronounced among men. Hence, men's mobility is among other things associated with increased autonomy in working life, while – in contrast to women – it does not seem to hamper their integration in the sphere of social reproduction.
Keywords: Europe; Temporary labour mobility; individualization; sphere of production; sphere of social reproduction; transnational division of labour

Visual Studies of Infrastructure: the case of the Belt and Road Initiative* (CLBrief, 2022)
Dennis Zuev* The Belt and Road Initiative (BRI) has become the largest infrastructure program in history, and has become a symbol of growing significance of China and its power.

Visuality and Infrastructure: The Case of the Belt and Road Initiative - Zuev, Dennis (The Palgrave Handbook of Globalization with Chinese Characteristics, 2023)

Coral empire: underwater oceans, colonial tropics, visual modernity: by Ann Elias Durham: Duke University Press, 2019, 296 pages ISBN: 9781478003182 (hbk) 99.95 USD, 9781478003823 (pbk) 26.95 USD, 9781478004462 (ebook) 26.95 USD - Zuev, Dennis (Visual Studies, 2023)